Going circular with what we wear and how we build: parallelisms between the Dutch and French catwalks of fashion and construction - Dytianquin, Norman; Paindavoine, Simon; Kalogeras, Nikos (Frontiers in Sustainability, 2024)
Responding to the call for circular transition, the Dutch and French governments aspire to achieve a fully circular economy by developing a transitional agenda in various sectors that include fashion and construction. The two countries are among the top 10 waste generators in the EU while the two sectors -fashion and construction -are the largest polluters in the EU. The aim of this study, and its main contribution, is to harmonize circular design principles which vary by sector into common types and identify the circular design principle which balances the sustainability dimensions the most. This responds to research gaps that merely describe these design principles applicable to different sectors, but which are silent as well on which achieves sustainability balance. Using multi-criteria decision analysis, selected case studies of companies in the two sectors and countries were scored and ranked according to environmental, economic, and social indicators of sustainability. The case projects were selected based on the circular design principle that the enterprises were applying. These principles were standardized for the two sectors to come up with five distinct types, namely, design for: (i) bio-based materials, (ii) service/ adaptability; (iii) disassembly, (iv) waste and material recovery, and (v) longevity. Three forms of triangulation were used to achieve reliability, validity and equivalence of the findings: (i) Data -by doubling the size of the sample cases to 40 establishments from 20; (ii) investigatorby having the authors score the projects separately; and (iii) method -by using two objective weighting methods in scoring the criteria. These techniques resulted in similar rankings of the cases in terms of triple bottom line scores per design principle. Designing for bio-based materials turned out to achieve the most balance. The case projects were also compared in terms of performance in achieving the UN Sustainability Development Goals (SDGs) which companies use to integrate sustainability with business. Circularity in fashion and construction primarily target responsible consumption and production, and climate action. A tertiary SDG was life on water and access to clean water for fashion; and life on land and sustainable cities for construction.